Innovative Governance Dalam Pelayanan Perpajakan (Studi Pada Penerapan Aplikasi E-Bphtb Di Bapenda Kabupaten Kuantan Singingi) - Vivin Delvya Roza; Yuliani, Febri; Adianto, Adianto (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2025)
This research is motivated by the government's need to innovate which emphasizes the use of creative ideas, technology, and new methods. This study aims to analyze and explain innovative governance in tax services in Kuantan Singingi Regency, as well as to identify inhibiting factors in the implementation of innovation in the form of the E-BPHTB application. This study uses the Sangkala innovative governance theory. This study uses a qualitative research method that is phenomenological approach that uses data collection techniques through interviews, observations and documentation. The results of this study indicate that the implementation of tax services has made a breakthrough in innovative governance in paying BPHTB taxes in the form of innovation in the form of the E-BPHTB application, but has not been implemented properly. Then the obstacles experienced are network limitations in using the E-BPHTB application, lack of IT experts and budget limitations in system development.